Market Driving and Performance : The Role of Dynamic Capabilities and Transformational Leadership - Wegert, Jan; Karlíček, Miroslav, 1979-; Machek, Ondřej, 1985-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Purpose: The objective of this doctoral dissertation is to explore the interplay of market driving, dynamic capabilities and transformational leadership, and their impact on performance. It aims to shed light on how firms engage in market driving, dynamic capabilities they deploy, and leadership they practice. Ultimately, this dissertation explores the empirical effect of their interplay on performance. Methodology: This doctoral dissertation adopts a mixed-method approach. Qualitative pre-research enables an exploration of the subjective experiences and perceptions of managers. The main quantitative research with 300 firms from the technological and start-up sector using PLS-SEM analysis allows empirical examination of the interplay between the key constructs, yielding statistically significant results and providing a more generalizable view of the relationships. Findings: The results underscore a strong positive influence of market driving on dynamic capabilities and transformational leadership, and moderate effect on firm performance. This supports the notion of market driving as an antecedent to dynamic capabilities and transformational leadership. Furthermore, the dissertation highlights the critical role of dynamic capabilities and transformational leadership as a mediator between market driving and firm performance, emphasizing its importance in translating market driving into performance. Based on qualitative pre-research, the extent firms engage in market driving, dynamic capabilities and transformational leadership varies depending on their business stage. Limitations: The generalizability might be constrained due to the research conducted in a single country and exclusively in the technology and start-up sector. The data were collected during and post Covid-19 crisis with possible impact on firms' behaviors. The reliance on self-reported measures might introduce potential biases.
Originality: This doctoral dissertation offers the empirical exploration of the relationships between market driving, dynamic capabilities, transformational leadership, and firm performance. Mixed-method approach enables an understanding of these complex relationships, providing both qualitative insights and empirical quantitative evidence.
Vedoucí práce: Miroslav Karlíček
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations